Ginsenoside Absorption Rate and Extent Enhancement of Black Ginseng (CJ EnerG) over Red Ginseng in Healthy Adults - Saebyul Yoo; Bom-I Park; Do-hyun Kim; Sooyoung Lee; Seung-hoon Lee; Wang-Seob Shim; Yong Ki Seo; Kimoon Kang; Kyung-Tae Lee; Sung-Vin Yim; Do Yu Soung; Bo-Hyung Kim (MDPI AG, 2021)
Red ginseng (RG) and black ginseng (BG, CJ EnerG) were prepared from fresh ginseng using one and nine cycles of steaming and drying, respectively. This process reduces the molecular weight (MW) of ginsenoside-active compounds in ginseng by removing sugar moieties from their dammaranes. We compared the pharmacokinetic characteristics of ginsenosides between BG comprising mainly low-MW ginsenosides (Rg3, Rg5, Rk1, and Rh1) and RG that predominantly contains high-MW ginsenosides (Rb1, Rb2, Rc, Rd, Re, and Rg1). The safety profiles and tolerability were also studied using a randomized, double-blind, single-dose, crossover clinical trial. A combination of Rb1, Rg1, and Rg3, well-known representative and functional RG components, exhibited a 1 h faster absorption rate (Tmax) and 58% higher exposure (24 h area under the concentration-time curve, AUC24) in BG than in RG. Furthermore, the combination of Rg3, Rg5, and Rk1, the major and most efficient components in BG, displayed 824% higher absorption (AUC24) in BG than in RG. The total ginsenoside showed a 5 h rapid intestinal absorption (Tmax) and 79% greater systemic exposure (AUC24) in BG than in RG. No clinically significant findings were observed in terms of safety or tolerability. Thus, BG extract was more effective than RG extract.